Implementation of Entrepreneurship Course through Fishery Product Defersification to Gen-Z in Nunukan - Ananda, Yosep Yuswanto Tri; Samsidar, Samsidar; Nasrudin, Abdul Rohman; Sinaga, Samuel Partogi Hasudungan; Ilham, Ilham; Alamsyah, Misdar; Fazli, Akhmad; Luthfiyah, Mardhiyatul; Iswan, Muhammad (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2025)
This activity focused on introducing diversification of processed fishery products. The target of this training is Gen-Z (junior high school students) in Nunukan Island so that they have additional insight into processed fishery products. This training activity is an implementation of the students' entrepreneurial spirit ability to enrich processed fishery products in the Nunukan Island area. This fishery product diversification training uses a participatory approach. The stages carried out are preparation, implementation, and closing. The preparation stage was used to design materials and practical materials that would be used during the training. The implementation stage was divided into two sessions. After being given a description of the material, pengabdi and the participants practiced making vannamei shrimp dumplings. The practice of making vannamei shrimp dumplings starts from the introduction of tools and materials to presentation. The participants and presenters made vannamei shrimp dumplings together. In this activity, questions and answers were also asked regarding the obstacles faced by participants during the making of vannamei shrimp dumplings. The implementation of the training was conducive and most participants were able to participate well. Participants were able to follow the training with enthusiasm and produce good products. Based on the response questionnaire, 100% stated that this kind of training on making processed fishery products needs to be held on an ongoing basis.